Impact of land-use change on catchment water balance: a case study in the central region of South Africa - Yali E. Woyessa (SpringerOpen, 2021)
Abstract An assessment study on the impact of land use change through afforestation on catchment water balance was carried out in one of the semi-arid quaternary catchments (C52A) of the Modder River Basin located in the central region of South Africa. The study used ArcGIS and the Soil and Water Assessment Tool (SWAT) to create scenarios of forest cover areas and to simulate the water balance of C52A, respectively. Climatic data from 1993 to 2020 were used to simulate the catchment water balance. The climatic data from 2011 to 2020 were generated using SWAT weather generator while the rest was obtained from South Africa Weather Service at three weather stations located within C52A catchment. In the C52A quaternary catchment it was envisaged to increase forest cover by considering afforestation on pastureland that is found on slopes > 8% and > 3% which created two forest scenarios. The baseline land use [Land use 2000 (LU2000)] which is taken as the base scenario in this study has about 84% of the catchment area covered with pasture. The two forest scenarios created were: forest scenario1 (FRSE1), i.e. conversion of pastureland on slope > 8% to forest, and forest scenario2 (FRSE2), i.e. conversion of pastureland on slope > 3% to forest. The type of forest considered in these scenarios is an evergreen tree, acronym as FRSE by SWAT land use classification. The conversion increased forest cover by 8.3% and 30.5% on FRSE1 and FRSE2, respectively. The result of the water balance of the catchment based on the land use scenarios were compared with the baseline land use scenario (LU2000). The result obtained showed that FRSE1 produced a non-significant change both on the mean monthly surface runoff and water yield compared to LU2000. On the other hand, FRSE2 showed 30% decrease on the mean monthly surface runoff, but increased the mean monthly lateral flow and base flow by 110% and 254%, respectively compared to the LU2000. Thus, in the overall water balance, the mean monthly water yield of the catchment increased by 171% on FRSE2 compared to the LU2000. Although there are considerable number of research reports on the negative effect of forest on catchment water yield, this study showed a significant water yield increase when approximately 30% of the C52A catchment area, which lay on slopes > 3% and covered by grass, was converted to evergreen forest land. The result showed that having a forest cover on a suitable slope range can bring about a positive effect on the total water yield of a catchment. Therefore, this finding is important for catchment management stakeholders and policy-makers when devising land use and water resources management strategies in a catchment.